Degloving Injury: Different Ways of Management - Nakarmi, Kiran K.; Shrestha, Sikshya Prakash (Journal of Nepalgunj Medical College, 2017)
Degloving injury involves shearing of the skin from the underlying tissue due to differential gliding in response to the tangential force applied to the surface of the body leading to disruption of all the blood vessels connected to skin. The flap of degloved skin has precarious blood supply making it almost impossible for the flap to survive. We describe two cases of degloving of thigh managed differently in different settings.